Violence against Iranian women as a cultural taboo: a hermeneutic study. Issue 4 (November 2016) - Heidari, Haydeh; Mardani-Hamooleh, Marjan
Abstract : Objective: Violence against women is a serious public health issue with negative effects, and it is a widespread problem. It affects the stability of the family. The purpose of this study was to explore the lived experiences of Iranian married women on violence against women. Study design: This qualitative research was carried out using a hermeneutic phenomenological approach. Participants and methods: We interviewed 11 married women to understand their experiences with regard to domestic violence against women. The seven-stage process of data analysis was used. Results: One constitutive pattern 'violence against women as a cultural taboo' and one associated theme, 'Living in pain and torment', were identified. Living in pain and torment also had two subcategories: living with fear and worry and living with sex inequality. Conclusion: The findings present a better understanding of the lived experiences of married women in Iran as regards violence against women. Nurses and other healthcare providers should be astute in identifying abused married women. They should evaluate the urgent physical, emotional, and sexual needs of these women.